STUDI KOLABORATIF DALAM PEMBANGUNAN PARIWISATA DI KAWASAN DERMAGA KERENG BANGKIRAI KOTA PALANGKA RAYA - Galadi (Journal Ilmu Sosial, Politik dan Pemerintahan, 2019)
This study raised collaborative issues in tourism development in the Kereng Bangkirai pier area of ??Palangka Raya City with the aim to determine the extent of collaboration carried out by the government, the private sector and the community in carrying out tourism development and to find out the inhibiting factors and supporters of collaboration in tourism development. The indicator in this study is to use the theory of Robert Agranoff and McGuire Michael (2003: 144-153) to view collaboration as activities that are horizontal and vertical. Then, the activity is analyzed through: (1) Communication (2) Value added (3) Deliberation. This type of qualitative research with a descriptive approach. The research location is in the tourist area of ??the Kereng Bangkirai pier, Palangka Raya City. The informants in this study were the Head of Tourism, Staff of the Attractiveness Section, Chairperson of the tourism awareness group, Community and Community Leaders with Data Collection Techniques through (1) observation, (2) interviews, (3) documentation. While the data analysis technique uses the version of Miles and Huberman in Sugiyono (2012), namely (1) data reduction, (2) data presentation, and (3) conclusion drawing / verification. As for the findings of the research, Collaboration conducted by the government, the private sector and the community in developing tourism uses: (a) Communication is the establishment of a forum and channel of communication that aims to provide mutual benefits including the formation of a tourism awareness group , also meetings that discuss tourism ; (b) Value added is the involvement of all elements in the tourism area of ??Kereng Bangkirai, both government, private and community; (c) Deliberation is a mutually beneficial cooperation between the government, the private sector and the community in the Kereng Bangkirai pier area, which results in positive changes in the form of mushrooming business premises in the form of stalls, shops, parking and provision of boat rental, water duck bikes, riverboats and photo booth. Supporting factors are: (a) Availability of infrastructure; (b) Budget availability; (c) Partnership; (d) Community participation. While the inhibiting factors (a) Limited human resources; (b) Budget limitations; (c) The condition of a pluralistic society.